2005
DOI: 10.1152/physrev.00002.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Physiology of Cardiac Repolarization

Abstract: The heart is a rhythmic electromechanical pump, the functioning of which depends on action potential generation and propagation, followed by relaxation and a period of refractoriness until the next impulse is generated. Myocardial action potentials reflect the sequential activation and inactivation of inward (Na(+) and Ca(2+)) and outward (K(+)) current carrying ion channels. In different regions of the heart, action potential waveforms are distinct, owing to differences in Na(+), Ca(2+), and K(+) channel expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
949
1
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 887 publications
(985 citation statements)
references
References 604 publications
22
949
1
13
Order By: Relevance
“…5A) and RA (Fig. 6A) blocked the effect of DCA to up-regulate I peak after diamide it is likely that the thioredoxin system controls Kv channels underlying this current, most likely Kv4.2, Kv4.3, and possibly Kv1.4 [43]. In contrast, the response of I ss to DCA after diamide was not altered by TrxR inhibitors (Fig.…”
Section: Differential Control Of K + Currents By Thioredoxin and Glutmentioning
confidence: 89%
See 1 more Smart Citation
“…5A) and RA (Fig. 6A) blocked the effect of DCA to up-regulate I peak after diamide it is likely that the thioredoxin system controls Kv channels underlying this current, most likely Kv4.2, Kv4.3, and possibly Kv1.4 [43]. In contrast, the response of I ss to DCA after diamide was not altered by TrxR inhibitors (Fig.…”
Section: Differential Control Of K + Currents By Thioredoxin and Glutmentioning
confidence: 89%
“…6B). Since Kv1.5 and Kv2.1 channels largely contribute to I ss in rat myocytes [43], it may be postulated that one or both are regulated by the glutaredoxin system, although accessory subunits may also be involved. Given that BCNU inhibits TrxR and GR to a similar degree (Fig.…”
Section: Differential Control Of K + Currents By Thioredoxin and Glutmentioning
confidence: 99%
“…In well‐studied channelopathies, mechanisms of dysfunction include defects in trafficking, channel assembly, and electrophysiological function, dependent on the location of the mutation 27, 28…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, or in addition, potassium current may play a functional role, as changes in potassium channel availability can dramatically alter the cardiac action potential [31]. Intriguingly, studies using heterologous expression systems have suggested that β1 may associate with and modulate, K v 4.3, which contributes to transient outward current (I to ) in human and mouse ventricle [32,33]. This interesting possibility will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%